2001
DOI: 10.1002/1521-3773(20010202)40:3<591::aid-anie591>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Hexaphyrin(1.0.1.0.0.0): An Expanded Porphyrin Ligand for the Actinide Cations Uranyl (UO22+) and Neptunyl (NpO2+)

Abstract: Applications of actinide chemistry, whether for energy or defense purposes, have left a legacy of potential waste hazards. The new expanded porphyrin ligand 1 forms stable complexes with both uranyl (UO22+) and neptunyl (NpO2+) ions and presents a potential new avenue for waste remediation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 151 publications
(37 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…Binding between UO 2 2+ and specific ligands, such as cyclic peptides [17,18], porphyrins [19,20], and naphthobipyrrole [21,22], is well known. We prepared a salicyladazine derivative as a ligand for UO 2 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…Binding between UO 2 2+ and specific ligands, such as cyclic peptides [17,18], porphyrins [19,20], and naphthobipyrrole [21,22], is well known. We prepared a salicyladazine derivative as a ligand for UO 2 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…6 Additionally, it was demonstrated that, with the exception of copper salts, isoamethyrin preferentially forms a coordination complex with the uranyl cation (e.g., 2) over other common metal salts.…”
Section: -6mentioning
confidence: 99%
“…Enzymes promote various chemical reactions through folding into three-dimensional ordered structures, by acting specifically with reactants, giving a high efficiency and selectivity. l -Proline was regarded as the simplest aldolase. It has been studied in many chemical reactions, for instance, intermolecular aldol reactions, Michael addition reactions, Diels–Alder reactions, and others. Aldol condensation is a kind of crucial C–C bond formation reaction, increasing the diversity and complexity of the molecules, and is applied in processing industry widely. l -Proline is a highly efficient catalyst for aldol reactions in organic solvents, while it is a poor catalyst in water. , However, in view of the environment, safety, and cost, carrying out aldol reactions in aqueous solutions with both high conversion and stereoselectivity is highly desired. , …”
Section: Introductionmentioning
confidence: 99%